Produção de soforolipídios por células imobilizadas de Candida bombicola ATCC 22214 em alginato de cálcio - Oliveira, Marcos Roberto de (2017)
Sopforolipids are biosurfactants produced by Candida bombicola ATCC22214 and have a wide field of application, but the high cost of production requires the development of more efficient bioprocesses to make them competitive. The objective of this research was to produce and verify the structural composition of the saporolipids by Candida bombicola, immobilized in calcium alginate. The immobilization process was standardized and the production of sophorolipids was tested by factorial design 43-1 been the factors: glucose, sunflower oil, K2HPO4 and CaCl2. Cellular immobilization was confirmed by MEV and sophorolipids characterized by FTIR and MS. The optimal conditions of immobilization were: 50 g/L cells; 30 g/L sodium alginate; 0.1 mol/L calcium chloride; curing time of 12 hours for 96 hours, reaching 2.33 g/L of sophorolipids with an immobilization efficiency of 74.487%. A new planning was carried out to optimize the production, wich reached 8.458 g/L and presented an immobilization efficiency of 90.922% under the conditions in (g/L): 30 glucose, 30 g of sunflower oil, 0.1 of yeast extract, 4.5 of K 2 HPO4 and 4.5 of CaCl2. The immobilized cells were stable for 3 cycles, maintaining efficiency around 70.7497%. The sappholipids presented the structural composition of 70.95% of acidic forms (7.92% C16, 12.54% C18, 37.29% C18:1 and 13.20% C18:2) and 29.05% of lactonic forms (5.8% C16, 3.63% C18, 17.82% C18:1 and 2.31 C18: 2).